Upper gastrointestinal bleeding in geriatrics - Sáez, Hugo (Cirugía del Uruguay, 1975)
Fifty cases of upper gastrointestinal haemorrhage in geriatric ulcer patients ( older than 65) are discussed. Fourteen cases were given only medica! treatment, with a mortality rate of 50 % . Thirty six of them were operated: 24 as an emergency procedure, with 6 deaths ( 25 % ) , and 12 had a delayed operation, with only one death. Gastrectomy has a high morbility and a 50 % mortality rate in emergency; this drops to 11 % when operation is delayed. Advisability and opportunity of the surgical treatment represent a great responsibility for ,the treating team. Minor or em·ergency procedures may be advisable in severa! cases.